El negro(a) en la pintura y la poesía de Max Jiménez - Alvarado Venegas, Ileana (2015)
The theme of Max Jimenez in his painting is mainly black and, above all, the black Cuban woman. Much of his work with this subject occurs between the decades of the thirties and forties of the twentieth century. Jimenez is considered an avant-garde, particularly expressionist, though his work also presents influence of other Vanguards, and is an expression of Latin American identity. In the same period, the black man and black woman as a motif in painting the Cuban avant-garde, it is uncommon as if it is in the case of Max Jimenez, who was not a Cuban national. This near absence of black as the theme of these Cuban artists, is notable for being the black important part of Cuban ethnic and cultural composition.With respect to poetry , Jimenez shows the same identification with Afro-Cuban , similar , at the time, which only shows the great mulatto poet Nicolas Guillen.In the comparison between poetry and painting Jimenez, the black man, especially black woman, is a central theme in his paintings , often tied to the land , often with a strong presence. In his poetry is not an issue that appears frequently because only dedicates three poems, but the place of enunciation and the attitude of the lyric speaker shows identification and involvement with black , black and culture as seen in his painting